Implementation in Handling Ex-Lepros Communities by The Social Service of Makassar City - Rizky Yulia Ilmi; Muh. Akmal Ibrahim; Suryadi Lambali (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This research aims to find out how the implementation of the development ex-leprosy Community by the social services of Makassar city. Starts from standards and targets of resource policies, inter-organizational communication, characteristics of implementing agents and strengthening activities in economic, social and political conditions. The research method used in this study is to use a qualitative descriptive method, namely the data obtained will be analyzed and then poured into a series of words, this technique aims to systematically describe the facts and data obtained. The results of this study indicate that there are still obstacles in the implementation of handling of the excluded community based on Makassar Mayor Regulation No. 89 Years 2016 carried out by the social services of the city of Makassar. problems related to work programs, provision of skills training and basic food assistance to the community are not implemented actively and meet the needs of the ex-leprosy community in the city of Makassar.